Assessment as learning: Lessons from the art and design studio. Issue 1 (1st March 2015) - Granville, Gary
The contemporary rhetoric of education policy is replete with references to problem solving, divergent thinking, learning from and through failure, risk-taking and similar desired qualities of education. Yet the connection between the 'new' rhetoric of education policy and the established language of art and design is rarely made. This is especially true in matters of student assessment. Perhaps the truth is that much of the rhetoric of education policy is presented in a deceptive discourse of criticality that masks an essentially different policy orientation: a 'command-economy' model of education. Educationists generally, and art and design educationists in particular, have been weak in challenging or at least questioning the new globalized orthodoxies. This article addresses the fault lines between these fields, with particular reference to the visual arts and suggests some options and implications for education policy. A brief introduction to the curriculum context in Ireland is provided in the first section. The second section comprises the main body: a discussion of fifteen principles of assessment that are derived from the literature of the past few decades. These fifteen principles are grouped in four categories and these are discussed in terms of their implications for curriculum structure and their resonance to with art and design education. The third and final section is a brief reflection on the potential of art and design education to inform general curriculum policy.